2017
DOI: 10.1016/j.bbacli.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of bronchoalveolar lavage fluid (BALF) from lung cancer patients using label-free mass spectrometry

Abstract: BackgroundLung cancer is the leading cause of cancer-related mortality in both men and women throughout the world. The need to detect lung cancer at an early, potentially curable stage, is essential and may reduce mortality by 20%. The aim of this study was to identify distinct proteomic profiles in bronchoalveolar fluid (BALF) and plasma that are able to discriminate individuals with benign disease from those with non-small cell lung cancer (NSCLC).MethodsUsing label-free mass spectrometry analysis of BALF du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 62 publications
(54 reference statements)
2
13
0
Order By: Relevance
“…Thus, many plasma proteins were detected in BALF, indicating that BALF is a great source of biomarkers for lung cancer. Indeed, these findings are in line with that of other studies published elsewhere (e.g., ANXA2) …”
supporting
confidence: 93%
See 3 more Smart Citations
“…Thus, many plasma proteins were detected in BALF, indicating that BALF is a great source of biomarkers for lung cancer. Indeed, these findings are in line with that of other studies published elsewhere (e.g., ANXA2) …”
supporting
confidence: 93%
“…[7] Recent studies have demonstrated potential usefulness of cancerassociated proteins, nucleic acid, and extracellular vesicles in the BALF for early detection and molecular characterization of lung cancer. [8][9][10] Proteomics is an emerging technology to quickly survey altered cellular functions through a large-scale gene determination and, therefore has been employed in a variety of clinical studies. [11,12] However, potential biomarker proteins in body fluids are often present at low levels, requiring sensitive techniques.…”
Section: Doi: 101002/prca201900028mentioning
confidence: 99%
See 2 more Smart Citations
“…However downregulation of the protein in cisplatin resistant esophageal cell line and lung cancer has also been reported (Lai, Chan et al 2016;Hmmier, O'Brien et al 2017). In the present study, the protein was upregulated following the treatments of Cur alone and synergistic combined treatment of Ox with using bolus administration but downregulated after the treatment of Ox alone.…”
Section: Discussionsupporting
confidence: 63%